Aristotle on perceiving objects - Marmodoro, Anna 1975- (Oxford University Press, 2014)
How can we explain the structure of perceptual experience? What is it that we perceive? How is it that we perceive objects and not disjoint arrays of properties? By which sense or senses do we perceive objects? This book investigates Aristotle's views on these and related questions